THE INFLUENCE OF BRAND TRUST, PRODUCT QUALITY, PRICE AND SOCIAL MEDIA MARKETING ON INTEREST TO REPURCHASE WARDAH COSMETIC PRODUCTS - Sri Nawangsari; Novia Ari Kusumawati (Jurnal Ekonomi, 2023)
The purpose of this study was to partially analyze the effect of brand trust, product quality, price and social media marketing on repurchase intention. The method of analysis in this study uses quantitative data and sources from primary data. The sampling technique used purposive sampling. Data collection was carried out by distributing questionnaires online and the samples used were respondents who bought and used Wardah cosmetic products at least once, where the number of samples used in this study was 100 respondents. Data analysis techniques were carried out by validity and reliability tests, classical assumption tests (normality test, multicollinearity test and heteroscedasticity test), multiple linear regression analysis, coefficient of determination (R2) and hypothesis testing (t test) with testing tools using the SPSS 25 program The results of testing the hypothesis in this study with the t test showed that the price and social media marketing variables partially had no effect on repurchase intention, while the brand trust and product quality variables partially had a significant effect on repurchase intention.